O ‘instinto’ modernista - Dionísio Vila Maior (Carnets, 2012)
In this reflection, I will try to devote a careful consideration to the crisis of values which characterized both late 19th and early 20th century. Recalling that crisis will force us to frame a picture where the value of the deterritorialization of the monologic speech prevails, endured by concepts such as subversion, pluridiscursivity and decadence. In addition, a mindful retrospection to the previously mentioned crisis will strengthen the need to conduct a sharp and precise historic-literary and theoretical-methodological evaluation, therefore allowing us better to apprehend the vanguardist ‘frame of mind’, which can be examined in light of particular aristotelic rationalism features such as exaggeration.